Progressive versus Nonprogressive Intracranial Dural Arteriovenous Fistulas: Characteristics and Outcomes - Hetts, S.W.; Tsai, T.; Cooke, D.L.; Amans, M.R.; Settecase, F.; Moftakhar, P.; Dowd, C.F.; Higashida, R.T.; Lawton, M.T.; Halbach, V.V. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: A minority of intracranial dural arteriovenous fistulas progress with time. We sought to determine features that predict progression and define outcomes of patients with progressive dural arteriovenous fistulas.MATERIALS AND METHODS: We performed a retrospective imaging and clinical record review of patients with intracranial dural arteriovenous fistula evaluated at our hospital.RESULTS: Of 579 patients with intracranial dural arteriovenous fistulas, 545 had 1 fistula (mean age, 45 extpm 23 years) and 34 (5.9%) had enlarging, de novo, multiple, or recurrent fistulas (mean age, 53 extpm 20 years; P = .11). Among these 34 patients, 19 had progressive dural arteriovenous fistulas with de novo fistulas or fistula enlargement with time (mean age, 36 extpm 25 years; progressive group) and 15 had multiple or recurrent but nonprogressive fistulas (mean age, 57 extpm 13 years; P = .0059, nonprogressive group). Whereas all 6 children had fistula progression, only 13/28 adults (P = .020) progressed. Angioarchitectural correlates to chronically elevated intracranial venous pressures, including venous sinus dilation (41% versus 7%, P = .045) and pseudophlebitic cortical venous pattern (P = .048), were more common in patients with progressive disease than in those without progression. Patients with progressive disease received more treatments than those without progression (median, 5 versus 3; P = .0068), but as a group, they did not demonstrate worse clinical outcomes (median mRS, 1 and 1; P = .39). However, 3 young patients died from intracranial venous hypertension and intracranial hemorrhage related to progression of their fistulas despite extensive endovascular, surgical, and radiosurgical treatments.CONCLUSIONS: Few patients with dural arteriovenous fistulas follow an aggressive, progressive clinical course despite treatment. Younger age at initial presentation and angioarchitectural correlates to venous hypertension may help identify these patients prospectively.CVDcortical venous drainageDAVFdural arteriovenous fistula